Reexamining Povarov Reaction’s Scope and Limitation in the Generation of HCV-NS4A Peptidomimetics - Maan T. Khayat; Abdelsattar M. Omar; Mahmoud A. Elfaky; Yosra A. Muhammad; Elaf A. Felemban; Khalid M. El-Say; Moustafa E. El-Araby (Heteroatom Chemistry)
Chronic Hepatitis C is a global health threat and a silent killer. Regardless of the profound progress in preventing and treating this disease, research continues to discover new direct antiviral agents (DAAs), especially against novel targets. Our research has been directed to leverage the NS4A binding site to develop peptidomimetic inhibitors of the hepatitis C virus (HCV) NS3 protease. In previous reports, we could provide evidence of tunability of this site by peptide and nonpeptide NS3/4A inhibitors. In this report, we used structure-based techniques to design 1,2,3,4-tetrahydro-1,7-naphthyridine derivative as NS4A core mimics that cover the region between residues Ile-25′ to Arg-28′. The synthetic plan featured the Povarov reaction as an efficient strategy to construct the 1,7-naphthyridine core. Although this reaction has been reported in many literatures, critical assessments for its scope and limitations are scarce. In our work, we found that Povarov was extremely sensitive to alkene and aldehyde reactants. Moreover, using pyridine amines was not as successful as anilines. The most striking results were the lack of stability of compounds during purification and storage. The four compounds that survived the stability problems (1a-1d) did not show significant binding potency with NS3, because their structures were too simple to resemble the originally planned compounds.